2006
DOI: 10.1210/me.2004-0389
|View full text |Cite
|
Sign up to set email alerts
|

OX1Orexin Receptors Activate Extracellular Signal-Regulated Kinase in Chinese Hamster Ovary Cells via Multiple Mechanisms: The Role of Ca2+Influx in OX1Receptor Signaling

Abstract: Activation of OX1 orexin receptors heterologously expressed in Chinese hamster ovary (CHO) cells led to a rapid, strong, and long-lasting increase in ERK phosphorylation (activation). Dissection of the signal pathways to ERK using multiple inhibitors and dominant-negative constructs indicated involvement of Ras, protein kinase C, phosphoinositide-3-kinase, and Src. Most interestingly, Ca2+ influx appeared central for the ERK response in CHO cells, and the same was indicated in recombinant neuro-2a cells and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(126 citation statements)
references
References 65 publications
4
119
0
3
Order By: Relevance
“…While little is currently understood about the mechanisms of regulation by the OX1R in GT1-7 cells, our results on phosphorylation of ERK1 and ERK2 are compatible with a recent study that demonstrated activation of ERK1/2 by orexin A in HEK-293T cells and in Chinese hamster ovary cells transfected with OX1R [59, 60]. …”
Section: Discussionsupporting
confidence: 92%
“…While little is currently understood about the mechanisms of regulation by the OX1R in GT1-7 cells, our results on phosphorylation of ERK1 and ERK2 are compatible with a recent study that demonstrated activation of ERK1/2 by orexin A in HEK-293T cells and in Chinese hamster ovary cells transfected with OX1R [59, 60]. …”
Section: Discussionsupporting
confidence: 92%
“…It has been well documented that intracellular protein kinase C (PKC) signaling pathway is involved in orexin receptorsmediated [Ca 2+ ] i mobilizing (1,14,22,23,33). We then determined whether orexin A regulates [Ca 2+ ] i of PFC neurons by modulation of PKC signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether the orexin-A-induced cell death also required de novo synthesis of mRNA, we treated CHO cells with an inhibitor of gene transcription, actinomycin D. At the concentration of 10 nM, actinomycin D only weakly affected cell viability, but it fully reversed orexin-A-induced cell death (Fig. 2B) (10,17) and activation of ERK, PKC, and PI3K (4,7,14). Chelation of intracellular Ca 2ϩ with 1 M BAPTA-AM significantly improved cell viability in response to thapsigargin, as expected, but did not affect orexin-A-mediated cell death (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, orexin receptors have been suggested to regulate cell plasticity. ERK (extracellular signal-regulated kinase) is strongly activated in CHO cells heterologously expressing OX 1 receptors (4,6,7). In the hippocampus, orexin receptors regulate synaptic plasticity (8).…”
mentioning
confidence: 99%